Beneficial effects of garlic on learning and memory deficits and brain tissue damages induced by lead exposure during juvenile rat growth is comparable to the effect of ascorbic acid. (3rd April 2017) - Ghasemi, Simagol; Hosseini, Mahmoud; Feizpour, Azadeh; Alipour, Fatemeh; Sadeghi, Akram; Vafaee, Farzaneh; Mohammadpour, Toktam; Soukhtanloo, Mohammad; Ebrahimzadeh Bideskan, Alireza; Beheshti, Farimah
Abstract: Objective : The neuroprotective effects of both garlic and ascorbic acid (AA) have been documented. In this study the effects of garlic and ascorbic acid on memory deficits and brain tissue oxidative damages induced by lead exposure was investigated. Methods : The juvenile rats were divided and treated: (1) Control, (2) Lead (lead acetate in drinking water, 8 weeks), (3) Lead – Ascorbic Acid (Lead-AA), (4)  Lead – Garlic (100 mg/kg, daily, gavage) (Lead-Gar). Results : In Morris water maze (MWM), the escape latency and traveled path in the Lead group were significantly higher while, the time spent in the target quadrant (Q1) was lower than Control. Both Lead-Gar and Lead-AA groups spent more times in Q1than to lead group. There were no significant differences in swimming speed between the groups. In passive avoidance (PA) test, the time latency for entering the dark compartment by Lead group was lower than Control. Treatment of the animals by AA and garlic significantly increased the time latency. In Lead group, the total thiol concentration in brain tissues was significantly lower while, MDA was higher than Control. Treatment by both garlic and AA increased total thiol concentrations and decreased MDA. Both garlic and AA decreased the lead content of brain tissues. Conclusion : It is suggested that treatment with garlic attenuates the learning and memory impairments due to lead exposure during juvenile rat growth which is comparable to AA. The possible mechanism may be due to its protective effects against brain tissues oxidative damage as well the lowering effects of brain lead content.